Der Wirkungsgrad von Training - Breitbart P; 2; Gärtner BC; Wolfarth B; Meyer T (Deutsche Zeitschrift für Sportmedizin)
Upper respiratory tract infections (URTIs) represent ahazard with highrelevance for elite athletes of all disciplines. They can lead to a reduction in performance and/or the necessity of a training/competition break. On average, each athlete experiences 3 URTIs per year with symptoms lasting for a mean of five days. Therefore, the intention of this review is to summarize the risk factors for URTIs, deduce preventive measures and give recommendations for return to sports to reduce re-infections and to avoid serious complications.The influence of training and competitive load on the risk of illness has been discussed controversially. There are indications that the frequency of infections seems to be increased shortly after a competition (open window-theory). URTIs occur more frequently in the winter months like in the general population. International air travelling was identified as the single biggest circumstantial risk factor for infections.An instrumental task of sports medicine is education of athletes about measures for infection prophylaxis and supervision of their implementation. A significant infection reduction is reached through compliance to general hygiene recommendations and a minimization of the contact with people outside the team in the hours after competition. Moreover, URTIs are prevented by an optimized planning of exercise load and travel as well as through vaccinations.Return to sports should not be allowed before a medical examination indicates the absence of generalized symptoms. This should typically include a determination of laboratory parameters and other organ-specific parameters (e.g. resting ECG). KEY WORDS: URTI, Physical Activity, Influential Factors, Illness Precautions, Infection Management